Comparison of H2 and NH3 Treatments for Copper Interconnects. (18th December 2013) - Chang, Yu-Min; Leu, Jihperng; Lin, Bing-Hong; Wang, Ying-Lung; Cheng, Yi-Lung
Abstract : The surface state, electrical, and reliability characteristics of copper (Cu) interconnects after ammonia (NH3 ) or hydrogen (H2 ) plasma treatment were investigated in this study. The experimental results show that H2 plasma treatment has excellent Cu oxide removal efficiency, less impact on the formation of Cu hillocks, and less damage on low-dielectric constant (low- k ) dielectrics in comparison to NH3 plasma treatment. However, H2 plasma treatment results in a higher leakage current between the Cu lines and shorter electromigration (EM) failure time due to a weaker adhesion strength at the Cu film interface. On the other hand, NH3 plasma treatment without the sufficient treatment time would lead to an increased probability of delamination at the Cu/barrier layer interface since the Cu oxide layer can not be completely removed. As a result, extending NH3 plasma treatment time can efficiently reduce the adhesion failure and enlarge EM resistance as well.